Two different cardiomyopathies in a single patient Hypertrophic cardiomyopathy and left ventricular noncompaction - ÖZBEN SADIÇ, BESTE; SÜNBÜL, MURAT (URBAN & VOGEL, 2013)
Hypertrophic cardiomyopathy is a complex and relatively common genetic disorder characterized by left ventricular (LV) hypertrophy, usually associated with a nondilated and hyperdynamic chamber with heterogeneous phenotypic expression and clinical course. On the other hand, LV noncompaction is an uncommon cardiomyopathy characterized by the persistence of fetal myocardium with a pattern of prominent trabecular meshwork and deep intertrabecular recesses, systolic dysfunction, and LV dilatation. We report a 29-year-old man with these two different inherent conditions. Our case raises the possibility of a genetic mutation common to these two clinical entities or different gene mutations existing in the same individual.
Keywords: Cardiomyopathy; Hypertrophic cardiomyopathy; Left ventricular noncompaction; MYOCARDIUM; MUTATIONS